If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(-29 + -5y) + -7y = 85 (-29 * 6 + -5y * 6) + -7y = 85 (-174 + -30y) + -7y = 85 Combine like terms: -30y + -7y = -37y -174 + -37y = 85 Solving -174 + -37y = 85 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '174' to each side of the equation. -174 + 174 + -37y = 85 + 174 Combine like terms: -174 + 174 = 0 0 + -37y = 85 + 174 -37y = 85 + 174 Combine like terms: 85 + 174 = 259 -37y = 259 Divide each side by '-37'. y = -7 Simplifying y = -7
| 3.25-x=-4.175 | | m-3m+4m+7= | | 4x-28=-60 | | .4x+.25(136-x)=42.16 | | (x+5)55=13x+8 | | 8-t=1 | | 2x+2x+10x-60+10x-60=240 | | 8y-28=100 | | (64w^2-49)=0 | | 8y+1=0 | | (16x^2y^2+72xy+81)=0 | | .4x+.25(122-x)=43.92 | | n^2-16n=66 | | -2x+4y=9 | | b^2-14b=-17 | | x(3x+4)=4x(x-1)+15 | | x^2+.25x-1.25=0 | | (16r^2-40r+25)=0 | | 3x^4(2x^2)= | | 7y+2(y-5)=3(y+2)-3 | | -0.8x=-12 | | 15y=-6+7+20y | | r^2+20r-80=-5 | | (x+2)(x-7)=(2x+7)(x-7) | | -1=x-7 | | -1=-7 | | (10c^2-33cd+20d^2)=0 | | v+4=-2 | | v^2+14v-71=-9 | | 12x+3=15x | | 15y+6-20y=7 | | 8x-6y=21 |